Assessment of spiritual suffering in the cancer context: A systematic literature review. Issue 5 (October 2015) - Best, Megan; Aldridge, Lynley; Butow, Phyllis; Olver, Ian; Price, Melanie; Webster, Fleur
Abstract: Objective: An important goal of cancer medicine is relief of patients' suffering. In view of the clinical challenges of identifying suffering patients, we sought to identify valid instruments for assessing the spiritual suffering of people diagnosed with cancer. Method: A systematic review of the literature was conducted in the Medline, Embase, the Cochrane Library, and PsycINFO databases seeking assessment instruments that measure either suffering or one of its synonyms or symptoms. The psychometric properties of the identified measures were compared. Results: A total of 90 articles were identified that supplied information about 58 measures. The constructs examined were: suffering, hopelessness/demoralization, hope, meaning, spiritual well-being, quality of life where a spiritual/existential dimension was included, distress in the palliative care setting and pain, distress or struggle of a spiritual nature. The Pictorial Representation of Illness and Self Measure (PRISM) (patient completed) was the most promising measure identified for measuring the burden of suffering caused by illness due to its ease of use and the inclusion of a subjective component. Significance of Results: Although the appropriateness of any measure for the assessment of spiritual suffering in cancer patients will depend on the context in which it is intended to be utilized, the PRISM is promising for measuring the burden of suffering due to illness.